Implementasi Model Pembelajaran PAKEM dalam Meningkatkan Pemahaman Nilai-Nilai Kristiani di Sekolah Dasar - Nofita R. Asbanu; Harun Natonis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The implementation of the PAKEM (Active, Creative, Effective, and Enjoyable Learning) model in Christian Religious Education (PAK) has shown significant potential in improving students’ understanding of Christian values ​​in elementary schools. This qualitative descriptive study analyzes the implementation of the PAKEM model and its effectiveness in fostering a deeper understanding of values ​​such as compassion, honesty, and forgiveness among students. Although conventional teaching methods are often used in PAK, the PAKEM model encourages active participation, creativity, and a fun learning atmosphere. Research shows that the model has a positive impact on students’ motivation and academic achievement. However, challenges such as limited teacher training and inadequate facilities hinder its optimal implementation. Solutions include ongoing professional development for teachers and adaptation of the curriculum to the local context. The study emphasizes the need for collaboration between educators, parents, and the community to support the effective implementation of the PAKEM model. Ultimately, the PAKEM approach not only improves cognitive outcomes but also contributes to students’ moral and spiritual development, preparing them to embody Christian values ​​in their daily lives. By cultivating an engaging and supportive learning environment, the PAKEM model aims to create a generation of morally resilient individuals who integrate their faith into their actions.